2022
DOI: 10.1021/jacsau.1c00568
|View full text |Cite|
|
Sign up to set email alerts
|

Mechanistic Insight into the Precursor Chemistry of ZrO2and HfO2Nanocrystals; towards Size-Tunable Syntheses

Abstract: One can nowadays readily generate monodisperse colloidal nanocrystals, but a retrosynthetic analysis is still not possible since the underlying chemistry is often poorly understood. Here, we provide insight into the reaction mechanism of colloidal zirconia and hafnia nanocrystals synthesized from metal chloride and metal isopropoxide. We identify the active precursor species in the reaction mixture through a combination of nuclear magnetic resonance spectroscopy (NMR), density functional theory (DFT) calculati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
49
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 17 publications
(63 citation statements)
references
References 73 publications
0
49
0
Order By: Relevance
“…Therefore, the first step in colloidal synthesis is usually the conversion of the precursors into the intended product. Given its importance, precursor conversion has been studied in many nanocrystal systems: metals, , metal sulfides and selenides, , metal oxides, lead halides, and metal pnictides. In such efforts, nanochemists aim to write down the complete and balanced chemical equation, after determining the correct stoichiometry of the reaction and identifying reaction by-products. Ideally, this is complemented with a rigorous kinetics study to obtain further details about the mechanism.…”
Section: Chemistry Of Precursor Conversionmentioning
confidence: 99%
See 4 more Smart Citations
“…Therefore, the first step in colloidal synthesis is usually the conversion of the precursors into the intended product. Given its importance, precursor conversion has been studied in many nanocrystal systems: metals, , metal sulfides and selenides, , metal oxides, lead halides, and metal pnictides. In such efforts, nanochemists aim to write down the complete and balanced chemical equation, after determining the correct stoichiometry of the reaction and identifying reaction by-products. Ideally, this is complemented with a rigorous kinetics study to obtain further details about the mechanism.…”
Section: Chemistry Of Precursor Conversionmentioning
confidence: 99%
“… While the above equation captures the zirconia formation, it is based on two assumptions: (1) the coordinated isopropanol participates in the reaction, and (2) the reaction proceeds through an S N 1 substitution mechanism, producing isopropyl chloride. We have recently shown that the reaction mixture contains mixed chloroalkoxide species: ZrCl 3 (O i Pr) and ZrCl 2 (O i Pr) 2 . These species are unreactive toward isopropanol, and thus only a stoichiometric amount of zirconium chloride is required in the reaction.…”
Section: Chemistry Of Precursor Conversionmentioning
confidence: 99%
See 3 more Smart Citations